2005
DOI: 10.1039/b501496d
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a bioactive calcia–silica sol–gel glass

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
91
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 26 publications
(32 reference statements)
13
91
0
Order By: Relevance
“…In addition to studying the structure and corresponding early stages of dissolution (stages 1 and 2), complementary diffraction studies have been conducted characterizing the formation of the silica-rich layer followed by amorphous calcium phosphate and HCA (stages 3-5) [54,61]. FitzGerald et al [53] designed a sample cell that enables XRD patterns to be continually collected from a 70S30C foam reacting in SBF on a synchrotron beamline.…”
Section: (C) Atomic Structure Of Sol-gel-derived Bioactive Glassmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to studying the structure and corresponding early stages of dissolution (stages 1 and 2), complementary diffraction studies have been conducted characterizing the formation of the silica-rich layer followed by amorphous calcium phosphate and HCA (stages 3-5) [54,61]. FitzGerald et al [53] designed a sample cell that enables XRD patterns to be continually collected from a 70S30C foam reacting in SBF on a synchrotron beamline.…”
Section: (C) Atomic Structure Of Sol-gel-derived Bioactive Glassmentioning
confidence: 99%
“…These techniques require major national/international facilities but can provide detailed information on glass structure. Conventional XRD, high-energy X-ray diffraction [53] and ND [54,55] measure the total diffraction pattern. It can sometimes be difficult to determine individual correlations from a single diffraction pattern owing to the overlapping correlation functions.…”
Section: (C) Atomic Structure Of Sol-gel-derived Bioactive Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrotron-based X-ray diffraction (XRD), for example, can show details about both crystalline phases and local atomic arrangement that conventional XRD cannot pick up, because of the higher flux and lower wavelength of exciting X-rays used. Jones & Skipper applied this technique to analyse the transformation of silicate bioceramics in SBF [84,109]; they showed Ca 2+ ions being continuously released and re-deposited on the material surface, and the formation of an octacalcium phosphate layer, followed by an amorphous layer that only after several hours crystallized into HCA ( figure 13). These results thus showed that surface reactions on these materials are more complex than originally hypothesized.…”
Section: (C) Synchrotron-based Techniquesmentioning
confidence: 99%
“…Under physiological conditions bioactive glasses dissolve in a controlled manner releasing calcium and phosphorous into solution. Ca and P form an amorphous calcium phosphate layer (ACP) which then crystallizes to form hydroxyapatite (HA) / Hydroxyl-carbonate apatite (HCA) [3,4] : the naturally occurring mineral present in both teeth and bones.…”
Section: Introductionmentioning
confidence: 99%